Drivers of and barriers to networked commercialisation: a business model perspective. (4th July 2019) - Mattila, Malla; Yrjölä, Mika; Lehtimäki, Hanna
The purpose of this study is to adopt a business model lens to identify and analyse key drivers of and barriers to the networked commercialisation of technology (NCT). The study contributes to commercialisation literature by illustrating the usefulness of the business model lens for analysing networked commercialisation. The results of the empirical case study of a company developing disruptive nanotechnological solutions for mass production identify key drivers of and barriers to business model decisions in the NCT. The results show that the tasks and activities involved in the NCT and business model development are connected to others operating in the business network.